Maliit na Bagay: Varying Transformations Under the New Normal - Baquiran, Romulo; Sanchez, Anna Felicia; Nadera, Victor Emmanuel Carmelo (Likhaan: The Journal of Contemporary Philippine Literature; Vol 15 No 1 (2021): Likhaan Journal of Contemporary Literature, Vol. 15, 2022)
N/A